Safety and efficacy of iodine-125 seed strand for intraluminal brachytherapy on ureteral carcinoma - Bi, Yonghua; Jiao, Dechao; Zhang, Jianhao; Ren, Jianzhuang; Han, Xinwei; Guo, Kefeng; Tu, Xueliang (Frontiers in Oncology, 2023)
Objective: To evaluate the safety and efficacy of iodine-125 seed strand for intraluminal brachytherapy on ureteral carcinoma. Methods: From November 2014 to November 2021, 22 patients with ureteral cancer not suitable for surgical resection were enrolled. Iodine-125 seed strand was inserted under c-arm CT and fluoroscopic guidance. The technical success rate, complications, disease control rate, and survival time were evaluated. Hydronephrosis Girignon grade and ureteral cancer sizes before and after treatment were compared. Results: A total of 46 seed strands were successfully inserted and replaced, with a technical success rate of 100% and median procedure time of 62 min. No procedure-related death, ureteral perforation, infection, or severe bleeding occurred. Minor complications were observed in 8 (36.4%) patients, and migration of seed strand was the most common complication. Six months after seed strand brachytherapy, 1 complete response, 3 partial responses and 5 stable diseases were evaluated, and the disease control rate was 64.3%. The Girignon grade of hydronephrosis was significantly improved 1 to 3 months after seed strand insertion. Disease control rates were 94.4%, 62.5%, and 64.3% at 1-, 3-, and 6-month follow up. Twenty patients were successfully followed up, with a mean follow-up of 18.0 ± 14.5 months. The median overall survival and progress-free survival were 24.7 months and 13.0 months, respectively. Conclusion: Iodine-125 seed strand is safe and effective for intraluminal brachytherapy, and can be used as an alternative to patients with ureteral carcinoma who are not suitable for surgical resection or systemic combined therapy.